"This is not your Life…and it becomes your Life": A Qualitative Exploration of Deployment‐related Stress and Support needs in National Guard and Reserve spouses who are Mothers of Young Children. Issue 4 (28th November 2020) - Ross, Abigail M.; DeVoe, Ellen R.; Steketee, Gail; Spencer, Renée; Richter, Meredith
Abstract : The adverse effects of deployment‐related stress (DRS) on military service members, spouses, and children are well documented. Findings from a recent Consensus Report on Military Families by the National Academies of Science, Engineering, and Medicine (2019) underscore the priority of gaining a more comprehensive understanding of the diversity of today's military families and their needs and well‐being. While social support is generally regarded as helpful during times of stress, it has not been studied extensively in National Guard/Reserve spouses who are parents of young children. This qualitative study of 30 women examines the unique ways in which DRS affects women who are National Guard/Reserve spouses and mothers of young children, as well as the processes through which they encountered support to manage these stressors. Salient themes spanned experiences involving deployment cycle phases of separation and reintegration and included both anticipated and unanticipated changes in family‐related division of labor, dynamics, and communication patterns. These were complicated by geographic, social, and cultural isolation and misguided efforts to support spouses initiated by civilians. Women managed these stressors primarily through seeking, acquiring, and repurposing existing sources of informal social support for themselves and formal supports for their children, with varying degrees of success. Resumen: Los efectos adversos del estrés relacionado con la movilización militar en los miembros del servicio militar, las esposas y los niños están bien documentados. Los resultados de un informe de consenso reciente sobre las familias de militares realizado por las Academias Nacionales de Ciencias, Ingeniería y Medicina [National Academies of Sciende, Engineering and Medicine (2019)] subrayan la prioridad de comprender de una manera más completa la diversidad de las familias de militares en la actualidad y sus necesidades y bienestar. Si bien el apoyo social generalmente se considera útil durante los momentos de estrés, no se ha estudiado ampliamente en las esposas de integrantes de la Guardia Nacional o de la Reserva Militar que son madres de niños pequeños. Este estudio cualitativo de 30 mujeres analiza las maneras únicas en las cuales el estrés relacionado con la movilización militar afecta a las mujeres que son esposas de integrantes de la Guardia Nacional o la Reserva Militar y madres de niños pequeños, así como los procesos por los cuales encontraron apoyo para manejar esos factores desencadenantes de estrés. Los temas destacados abarcaron experiencias relacionadas con las fases de separación y reintegración del ciclo de movilización militar e incluyeron los cambios tanto previstos como imprevistos en la división de los patrones de trabajo, de dinámica y de comunicación relacionados con la familia. Estos se complicaron por el aislamiento geográfico, social y cultural y los esfuerzos equivocados que hicieron los civiles para apoyar a las esposas. Las mujeres manejaron estos factores desencadenantes de estrés principalmente mediante la búsqueda, la adquisición y la readaptación de fuentes existentes de apoyo social informal para ellas y de apoyo formal para sus hijos, con diversos grados de éxito. 摘要: 有充分证据证明服役相关的压力(DRS)对军人、配偶和子女的不利影响。美国国家科学、工程和医学研究院(2019年)最近发布了一份关于军人家庭的共识报告，文中的研究结果强调，首先要更全面地了解当今军人家庭的多样性，以及他们的需求和福祉。虽然通常人们会认为社会支持在压力时期是有帮助的，但在身为幼儿父母的国民警卫队/预备役配偶中，社会支持尚未得到广泛研究。这项针对30名女性的质的研究探讨了DRS对身为国民警卫队/预备役配偶和幼子母亲的妇女的独特影响，以及她们在处理这些压力源时获得支持的过程。突出的主题跨越了涉及分离和重返社会的兵役周期阶段的经验，包括与家庭相关的劳动分工、动态和沟通模式中预期的和未预期的变化。由于地理、社会和文化上的孤立以及由平民发起的支持军人家庭配偶的错误努力，这些问题变得复杂起来。妇女管理这些压力源主要是通过寻求、获得和重新利用现有的非正式社会支持资源，为自己和为子女提供正式的支持，取得了不同程度的成功。